(untitled) - Gilbert, Harry (Đồng Nai, 2009)
In our world today a hummingbird is a small, brilliantly coloured bird that lives in the tall trees of tropical forests. In the far distant future, Hummingbird (Hummy for short) is a girl of sixteen who lives somewhere in the Galaxy, on a planet called Just Like Home. She has the name 'Hummingbird' in big letters on all her clothes, but she has never seen a real hummingbird. She has never seen any living animal or bird at all. The Book of Remembering says that there were once many animals on a planet called Earth, but that was before the Burning, a long, long time ago ...
Keywords: English language,Ngôn ngữ tiếng Anh,Short stories,Truyện ngắn; Readers,Người thích đọc sách